Uji Validitas, Struktur Internal, dan Measurement Invariance pada Alat Ukur Achievement Goal Orientation - Jamaludin Jamaludin (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2019)
AbstractAchievement goal orientation (AGO) is the goal orientation to achieve achievement. This study aims to explore information about the achievement goal orientation (AGO) measurement tool. This study combines two AGO measurements (original and revised) developed by Midgley et al (1998, 2000) based on the Manual for the patterns of adaptive learning scales (PALS). In this study only measured two of the three dimensions analyzed, namely AGO performance and AGO mastery. The sample in this study amounted to 544 people from three junior high schools in West Jakarta. Twenty-one items (10 items AGO performance and 11 items AGO mastery) were tested for validity, internal structure, and invariance measurement. The results of the validity of the CFA found that AGO performance and AGO mastery were not appropriate to measure the dimensions of AGO. Based on the results of internal structure analysis, the bifactor model is more valid and appropriate in measuring AGO performance and AGO mastery. The results of the Bifactor AGO performance analysis are divided into factors of "doing your best" and "looking smart" while AGO mastery is divided into "liking the task" and "understanding the task". There are only five AGO performance items and seven unidimensional AGO mastery items. In the inter-gender validity test, it was found that men are oriented towards AGO performance while women are oriented towards AGO mastery. MGCFA analysis results that AGO performance is valid up to the metric invariance stage while AGO mastery is not invariance.AbstrakAchievement goal orientation (AGO) adalah orientasi tujuan untuk mencapai prestasi. Penelitian ini bertujuan untuk mengeksplorasi informasi mengenai alat ukur achievement goal orientation (AGO). Penelitian ini menggabungkan dua pengukuran AGO (original dan direvisi) yang dikembangkan oleh Midgley et al (1998, 2000) berdasarkan Manual for the patterns of adaptive learning scales (PALS). Pada penelitian ini hanya mengukur dua dari tiga dimensi yang dianalisis yaitu AGO performance dan AGO mastery. Sampel pada penelitian ini berjumlah 544 orang dari tiga sekolah menengah pertama di Jakarta Barat. Keduapuluh satu item (10 item AGO performance dan 11 item AGO mastery) diuji validitas, struktur internal, dan measurement invariance. Hasil validitas CFA ditemukan bahwa AGO performance dan AGO mastery tidak sesuai mengukur dimensi AGO. Berdasarkan hasil analisis struktur internal, model bifaktor lebih valid dan sesuai dalam mengukur AGO performance dan AGO mastery. Hasil analisis bifaktor AGO performance terbagi menjadi faktor “melakukan yang terbaik” dan “terlihat pintar” sedangkan AGO mastery terbagi menjadi “menyukai tugas” dan “memahami tugas”. Hanya terdapat lima item AGO performance dan tujuh item AGO mastery yang bersifat unidimensional. Pada uji validitas antar gender, dihasilkan bahwa laki-laki berorientasi pada AGO performance sedangkan perempuan berorientasi pada AGO mastery. Analisis MGCFA dihasilkan bahwa AGO performance valid sampai tahap metric invariance sedangkan AGO mastery tidak invariance.